Lactate, rather than ketones, may provide alternative cerebral fuel in hypoglycaemic newborns. Issue 2 (4th September 2014) - Harris, Deborah L; Weston, Philip J; Harding, Jane E
Abstract : Objective: Alternative cerebral fuels are reputed to provide neuroprotection during hypoglycaemia, particularly in breastfed babies. We measured concentrations of alternative cerebral fuels in hypoglycaemic babies in the first 48 h. Patient and methods: Babies were ≥35 weeks, ≤48 h old and at risk of hypoglycaemia (infant of diabetic, preterm, small or large). Plasma glucose, β-hydroxybutyrate, lactate and insulin concentrations were measured in babies who had been hypoglycaemic (<2.6 mM) for >1 h. Results: Samples were taken from 35 hypoglycaemic babies at 3.7; 1.8–39.6 (median; range) hours after birth. Concentrations of glucose and β-hydroxybutyrate were low (2.03; 0.19–3.39 mM and 0.06; 0.00–1.20 mM), but lactate concentrations varied widely (3.06; 0.02–7.96 mM). Infants of diabetics had lower β-hydroxybutyrate and higher insulin concentrations, but mode of feeding did not influence plasma concentrations of alternative cerebral fuels. Conclusions: Hypoglycaemic babies within the first 48 h after birth are unlikely to receive neuroprotection from ketones. However, lactate may provide an alternative cerebral fuel for many. Lactate, rather than ketones, may provide alternative cerebral fuel in hypoglycaemic newborns. Trial registration number: ACTRN12608000623392.